Biological rhythms in premenstrual syndrome and premenstrual dysphoric disorder: a systematic review - Adile Nexha; Luisa Caropreso; Taiane de Azevedo Cardoso; Jee Su Suh; André C. Tonon; Benicio N. Frey (BMC, 2024)
Abstract Background Women with premenstrual syndrome (PMS) and premenstrual dysphoric disorder (PMDD) typically experience a range of psychological and physiological symptoms that negatively affect their quality of life. Disruption in biological rhythms, including alterations of the sleep-wake cycle, have been implicated in PMS/PMDD, though literature is still growing to substantiate these findings. The objective of this study is to systematically review the available literature on biological rhythms disruption in PMS/PMDD. Methods A literature search was conducted on four databases (Pubmed, Embase, Medline, and Web of Science) on December 3rd, 2021. This search yielded a total of 575 articles that assessed the relationship between biological rhythms and PMS/PMDD/premenstrual symptoms. Results After the exclusion of irrelevant articles and hand-searching references, 25 articles were included in this systematic review. Some studies showed that women with PMS/PMDD present lower melatonin levels, elevated nighttime core body temperature, and worse subjective perception of sleep quality when compared to women without PMS/PMDD. Other biological rhythms parameters showed either no differences between groups (wrist actimetry) or conflicting results (objective sleep parameters, cortisol, prolactin, and thyroid stimulating hormone). Conclusion Current research demonstrates that women with PMS/PMDD experience lower melatonin levels, higher body temperature, and worse subjective perception of sleep quality. This review outlines some possible mechanisms behind these findings and proposes recommendations for future research. This systematic review was registered in the International Prospective Register of Systematic Reviews (PROSPERO) under registration number CRD42020149921.